고유변동성 요인에 대한 위험평가 - 김수경(Sookyung Kim); 변영태(Youngtae Byun); 김우현(Woohyun Kim) (한국콘텐츠학회 논문지, 18(10), 2018)
In this study, we examined whether common idiosyncratic volatility(CIV), a risk factor for idiosyncratic volatility, can be evaluated as a pricing factor. The sample is listed on the Korea Exchange. The analysis period is 288 months from July 1992 to June 2016. The main results of this study are as follows. First, in the empirical verification of the market excess returns of the testing portfolios, the difference in the return on the CIV factor sensitivity difference was statistically significant. In other words, we confirmed that there is a risk premium for CIV factors. Second, CAPM, FF3 factor model, and FF5 factor model do not explain the risk premium for CIV factors, whereas factor models that add CIV factors explain the risk premium for CIV factors. In other words, the CIV factor can be evaluated in terms of pricing factors. 본 연구는 국내 주식시장을 대상으로 고유변동성을 위험요인으로 산출한 CIV(common idiosyncratic volatility)요인이 가격결정요인으로 평가될 수 있는지를 검증하였다. 분석기간은 1992년 7월부터 2016년 6월까지로 설정하였으며, 총 288개월간의 월별 자료를 이용하였다. 본 연구의 주요 실증결과는 다음과 같다. CIV요인 계수를 기준으로 구성된 검증포트폴리오들의 CIV요인민감도 차이에 따라 통계적으로 유의한 수익률 차이를 보임으로써 CIV요인에 대한 위험프리미엄이 존재하는 것을 확인하였다. 또한, CIV요인에 대한 위험프리미엄은 기존의 요인모형들에 CIV요인을 추가함으로써 잘 설명되는 것으로 나타났다. 결과적으로 CIV요인은 유의한 위험프리미엄을 가지고 있으며 가격결정요인의 관점에서 평가가 가능한 것으로 판단된다.